O-011 UK National Prospective Flow Diverter Registry of Aneurysm Treatment: First 200 patients - Safety and efficacy findings. (14th July 2013) - White, P; Molyneux, A
Abstract : Background: Flow diverters (FD) offer a novel approach to the endovascular management of aneurysms. In a small minority FD may be the only therapeutic option for previously untreatable lesions but in most patients they have actually been used as an alternative to established therapeutic strategies. Data are currently limited to small prospective studies, single centre series and retrospective analysis of (mostly small) existing case series. Issues have arisen with FD devices around non-procedural bleeding from previously unruptured aneurysms, high technical complication rates, delayed parent vessel stenosis/occlusion and parenchymal bleeds apparently unrelated to dual antiplatelet therapy or any procedural event. Caution should be exercised with the introduction of any novel class of device and comprehensive post marketing surveillance programmes are required by FDA and European Regulators alike. In late 2009 the UK Medicines and Healthcare Regulatory Agency (MHRA) expressed "interested concern" over FDs and unexpected SAEs (serious adverse events), which had occurred with FDs. In response to these concerns, a prospective Registry was proposed by UK Neurointerventional Group (UKNG) members in early January 2010 and endorsed by the wider UKNG as a means to address many of the concerns. More recently entering UK PED ™ cases into the Registry has been mandated by NICE in its recommendations regarding used of PED ™ . Methods: UK wide audit Registry was developed- funded by one industry partner (Covidien) - but run completely independently in three academic institutions- University of Edinburgh, Newcastle University, University of Oxford. A simple, workable "case record form" (CRF) was developed, which collected a minimum demographic, procedural and follow-up set of data. CRF uses online data entry and audit has run prospectively from November 2010. However, two large scale FD users (University College London & QE Hospital Birmingham) were enabled to put in their prospectively acquired 2010 cases. Formal statistical analysis was undertaken independently of database administration by Oxford Neurovascular and Neuroradiology Research Unit (ONNRU). Only the database administrator can access all the anonymised data. The project was scrutinised by Scottish Ethics Committee who decided it constituted prospective audit of anonymised data. Results: All 29 UK neuroscience centres with a formal INR service (three with no on site INR service were not approached) were contacted and invited to participate. Two centres did not respond but from informal discussions one of these didn't use FDs (to end of 2011) and the remaining centre used quite modest numbers (low single figures to end of 2011). Of the 27 centres responding, 2 don't use FD's, leaving 25 centres participating in the registry (representing 96% of UK centres using FD for aneurysm treatment). We will report the statistical results on the first 200 patients enrolled in the Registry. Conclusion: A very diverse group of patients and aneurysms were enrolled but they do represent "real world" practice and outcomes. The complication rates observed were not insignificant but analysis by aneurysm type/size/location/symptomatology is critical to evaluating the ongoing role of FDs in aneurysm therapy. Disclosures: P. White: 1; C; Covidien, Codman, Microvention, Acandis. 2; C; Codman, Microvention. A. Molyneux: 1; C; Covidien.